Liebhard Egkenfelder und die Musikhandschriften in Pressburg in der zweiten Hälfte des 15. Jahrhunderts - Eva Veselovská (Musicologica Brunensia, 2020)
Almost all preserved musical manuscripts from the 15th century from Bratislava belonged to the Library of Bratislava Chapter. A small part of manuscripts and fragments came from other parish, monastery and school libraries or from private collections. Complete liturgical codices and fragments are a testimony of the multicultural background of customers, makers, and users. The most precious materials from the second half of the 15th century are the liturgical manuscripts of the Bratislava Chapter - Bratislava Antiphonary IIa and IIb (Strigonium liturgy, Austrian scriptorium and illumination tradition) and Bratislava Antiphonary III (Strigonium liturgy, Buda-Renaissance scriptorium in combination with the Austrian illumination school). One of the most interesting personalities from Late Middle Ages Bratislava was a notary Liebhard Egkenfelder. He was the main scriptor in town between 1441 and 1456. He was an extraordinarily erudite layman and a great humanist representative. He owned a large private library with codices from various scientific disciplines. He himself copied several manuscripts. Amongst the codices he wrote "with his own hand" we can find material regarding both liturgical and secular music culture.